Low-Grade Endometrial Stromal Sarcoma in a 22-Year-Old Maiden Female: A Rare Case Report from Syria - Lana Nseir; Georget Mansour; Junior Makhoul; Luna Skaf; Mohammad Ziad Dahhan; Zuheir AlShehabi (Case Reports in Obstetrics and Gynecology)
Endometrial stromal sarcoma (ESS) is a rare and challenging type of endometrial tumor, constituting only about 0.2% of all uterine malignancies and occurring in women 42–58 years of age. ESS is usually misdiagnosed as leiomyoma. They both have nonspecific symptoms, which makes the diagnosis of ESS difficult to achieve. As the ESS is infrequently encountered, optimal management is quite debatable. Here, we report a rare case of a 22-year-old Syrian female who presented with abnormal uterine bleeding; the preoperative diagnosis suggested leiomyoma while histopathological and immunohistochemical studies confirmed the diagnosis of LG-ESS stage IIA. Therefore, the treatment plan was shifted from a conservative myomectomy to a total hysterectomy with both adnexa. The aim of this case report is to draw attention to this uncommon tumor at young age of patients as well as to have awareness of the necessity to suspect this diagnosis especially with the presentation of rapid enlargement of uterine leiomyoma.